Transmediale Überschreitung der Fiktionsgrenzen: Lars Kraumes Medienpuzzle "Keine Lieder über Liebe" - Hollerweger, Elisa (Studia Germanica Posnaniensia, 2014)
The essay thematises Lars Kraume`s multimedia experiment “Keine Lieder über Liebe” produced in 2005 starring Heike Makatsch, Jürgen Vogel and Florian Lukas. The story was developed in songs written by the fictive “Hansen Band”, in a film without a script and in a retrospective diary from one of the main characters and revolves around the question “How well do you know the people you are living with?”. The single media representations and their complex interaction can be seen as a challenge for intermedia theory and will be systematically explored in the following sections. After a short overview of the background of emergence, the analysis focuses on narrative structures and coherences of songs, film and book, on the dynamic of characters and plots and on the blurred boundaries between fiction and reality. Thereby it is interesting, in which way the eponymic negation of a medialization of love and the cross-media game of deception complement each other.